Multidimensional capital dynamics in poverty alleviation: evidence from Kalasin Province, Thailand - Kaewhanam, Kathanyoo; Kaewhanam, Phimlikid; Purnomo, Eko Priyo; Intanin, Jariya; Kamolkat, Sirinada; Pinitdanklang, Kanoknet; Pongsiri, Ariya (Frontiers in Political Science, 2025)
IntroductionThis study examines the dynamic influence of multidimensional capital on poverty alleviation in Kalasin Province, Thailand, a region characterized by persistent poverty. The Sustainable Livelihood Framework (SLF) and Public Policy Implementation Theory are applied to capture changes in human, physical, financial, natural, and social capital across 2020-2023.MethodsA longitudinal quantitative design was employed using multi-stage stratified random sampling. Data were collected from 9,389 households per year (2020, 2021, 2023). Analyses included descriptive statistics, one-way ANOVA, Scheffé post hoc tests, and MPI construction with EFA validation. Ethical approval was obtained from Kalasin University IRB.ResultsFindings show significant temporal variations in the effects of all capital forms in 2020 and 2023, with stagnation in 2021. Human and social capitals demonstrated resilience, while financial, physical, and natural capitals fluctuated with policy and economic cycles.DiscussionThe integration of SLF and Public Policy Implementation Theory highlights the role of institutional capacity in mediating capital effectiveness. Capital influences are dynamic rather than static, shaped by policy sequencing, governance quality, and socio-economic context.ConclusionMultidimensional capital is temporally elastic and context-dependent. Adaptive, evidence-based, multi-capital policy strategies are required for sustainable poverty reduction.